2006
DOI: 10.1177/0886260506293482
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Gender Atypicality, Victimization, and PTSD Among Lesbian, Gay, and Bisexual Youth

Abstract: This study examined childhood gender atypicality, lifetime victimization based on sexual orientation, and current mental health, including trauma symptoms and posttraumatic stress disorder (PTSD), among 528 lesbian, gay, and bisexual youth. Nearly 80% reported verbal victimization, 11% physical, and 9% sexual, with males reporting significantly more victimization. Victimization began, on average, at age 13. Verbal attacks occurred as early as age 6, physical attacks at 8, and sexual attacks at 9. Youth who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
390
6
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 493 publications
(432 citation statements)
references
References 11 publications
31
390
6
5
Order By: Relevance
“…Previous research has found a relationship between disclosure of sexual minority orientation at work and perceived discrimination [31] and multiple studies on sexual minority youth show that they frequently experience discriminatory events in school settings due to their sexual orientation, particularly boys [13,32,33]. These two forms of institutional and interpersonal discrimination are significant problems for SMM, and the current study suggests that this may even be associated with intentions to engage in sexual behavior, again perhaps as a coping strategy.…”
Section: Heterosexism and Sexual Behavior In Smmmentioning
confidence: 67%
“…Previous research has found a relationship between disclosure of sexual minority orientation at work and perceived discrimination [31] and multiple studies on sexual minority youth show that they frequently experience discriminatory events in school settings due to their sexual orientation, particularly boys [13,32,33]. These two forms of institutional and interpersonal discrimination are significant problems for SMM, and the current study suggests that this may even be associated with intentions to engage in sexual behavior, again perhaps as a coping strategy.…”
Section: Heterosexism and Sexual Behavior In Smmmentioning
confidence: 67%
“…First, childhood trauma, including psychological, physical and sexual abuse are more likely to be experienced amongst sexual minority status groups (Austin et al, 2008;Hatzenbuehler, 2011;Roberts et al, 2010;Roberts, Glymour & Koenen, 2013;Wilson & Widom, 2010), and abuse in childhood is linked to greater victimisation in adulthood (Balsam et al, 2005) and to revictimisation (Balsam, Levahot & Beadnell, 2011). Furthermore, victimisation from abuse in childhood is also associated with gender nonconformity behaviours in children (Roberts, Rosario, Corliss, Koenen & Austin, 2012), and sexual orientation victimisation with gender atypicality amongst adolescents (D'Augelli, Grossman & Starks, 2006). Second, minority stress in the form of the sexual prejudice (Herek, 2000;Savin-Williams, Pardo, Vrangalova, Mitchell & Cohen, 2010;Hatzenbuehler, 2009;Meyer, 2003), stigma and social exclusion sexual minority status groups are exposed to can have a deleterious effect on psychological and physical health, and is associated with risk-taking behaviours linked to greater victimisation risk (Boehmer, Miao, Linkletter & Clark, 2012;Bontempo & D'Augelli, 2002;Cochran, 2001;Cochran & Mays, 2009;D'Augelli, 2003;Goodenow, Netherland & Szalacha, 2002;Hatzenbuehler, 2009;Meyer, 2003;Paul et al, 2002;Robin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Voor transgenderjongeren is het een uitdaging om hun genderidentiteit in te passen in hun persoonlijke karakteristieken en in de traditionele verwachtingen die er in de maatschappij bestaan ten aanzien van hun biologische sekse. Uit Amerikaans onderzoek blijkt dat jongeren die als gender atypisch werden beschouwd tijdens hun kinderjaren een hogere mate van slachtofferschap en meer gezondheidsproblemen rapporteren (D'Augelli, Grossman, & Starks, 2006). Dit wordt onderschreven in studies waaruit blijkt dat transgenders problemen ervaren ten aanzien van hun acade-mische prestaties (Greytak, Kosciw, & Diaz, 2009) en geconfronteerd worden met zowel fysiek als seksueel misbruik, suïcidaliteit en psychiatrische stoornissen (Clements-Nolle, Marx, & Katz, 2006;Cole, O'Boyle, Emory, & Meyer, 1997;Devor, 1994;Rutgers WPF, 2011;Rutgers WPF, 2013;SCP, 2012).…”
Section: Ervaren Stigmatisering En Sociale Steun Bij Jonge Transgendersunclassified